2016
DOI: 10.1519/jsc.0000000000001230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Energy Expenditure During Single-Set vs. Multiple-Set Resistance Exercise

Abstract: The purpose of this study was to compare energy expenditure (EE) of single-set and multiple-set resistance exercise protocols using indirect calorimetry. Twelve men and twelve women (age = 21.4 ± 1.3 years) performed a single-set (SS) and multiple-set (MS) resistance exercise protocol in random order. The subjects performed two protocols at 70% of their 1-repetition maximum. The protocols consisted of 5 upper-body exercises of either 1 or 3 sets per exercise performed in random order. Metabolic and cardiorespi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Results showed no significant difference in total body fat reductions, determined by DXA, between protocols. Collectively, these results indicate that greater RT volumes do not result in greater decrease in body fat, even though greater volume RT programs elicit a higher energy expenditure [15,17,27]. The lack of a significant difference in body fat changes is possibly due to an insufficient difference in training stimuli provided between the prescribed exercise training protocols (3 vs. 6 sets per exercise, 1 vs. 3 sets per exercise, 2 vs. 3 training days per week).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Results showed no significant difference in total body fat reductions, determined by DXA, between protocols. Collectively, these results indicate that greater RT volumes do not result in greater decrease in body fat, even though greater volume RT programs elicit a higher energy expenditure [15,17,27]. The lack of a significant difference in body fat changes is possibly due to an insufficient difference in training stimuli provided between the prescribed exercise training protocols (3 vs. 6 sets per exercise, 1 vs. 3 sets per exercise, 2 vs. 3 training days per week).…”
Section: Discussionmentioning
confidence: 82%
“…RT frequency has shown a dose-response relationship to muscular adaptations with higher frequencies showing greater adaptations [6,42,49]. Additionally, training volume has shown a dose-response effect on energy expenditure with greater volume sessions showing a higher energy expenditure when compared to lower volume sessions [15,17,27]. Heden et al [17] observed that 3 sets of a whole-body RT session (10 exercises at a 10-repetition maximum) expended more than two times the energy compared to the same program performed with 1 set.…”
Section: Effects Of Different Resistance Training Frequencies On Fat mentioning
confidence: 99%
“…More recently, Mookerjee et al () compared EE using a circuit training method (1 set) and multiples set (3 sets). Twelve men and twelve women performed a CT and a TT resistance exercise protocol in a random order.…”
Section: Discussionmentioning
confidence: 99%
“…The PEDro Score Scale range from 0 to 10 points, with 6 indicating a score of high quality (HQ), while lower when compared with 6 indicates low quality (LQ). After classification using the PEDro scale, eight studies (Hunter et al, 2003;Farinatti et al, 2009;Kelleher et al, 2010;Farinatti & Neto Castinheiras, 2011;Heden et al, 2011;Aniceto et al, 2013;Cesar et al, 2013;Mookerjee et al, 2016) were used in the meta-analysis (Table 1).…”
Section: Methodological Quality and Strength Of Evidence For Meta-anamentioning
confidence: 99%
“…The analyzer was calibrated according to the manufacturer. The VO2 was also measured over 5 minutes at the end of the session 19 . The VO2 was collected breath-by-breath and averaged in 10-second intervals.…”
Section: Energy Expenditurementioning
confidence: 99%